Effect of KWL Strategy (Know, Want, Learn) on Reading Ability of Grade IV Elementary Students: Literature Study: Pengaruh Strategi KWL (Know, Want, Learn) Terhadap Kemampuan Membaca Pemahaman Siswa Kelas IV SD : Studi Literatur - Nurlisa, Nurlisa; Salahuddin, Amar; Oktasusilawati, Wiwik (Journal of Vocational Education and Information Technology (JVEIT), 2023)
This research is attracted by the condition where students have poor reading comprehension. This occurs because the students solely read given texts, in which students are active in reading. Hence, it is difficult for students to conclude the text. Therefore, an appropriate strategy is needed to overcome these problems. KWL Strategy (Know, Want, Learn) is an effective strategy applied to the learning process, especially reading comprehension. The KWL (Know, Want, Learn) strategy provides an active role for students before, during, and when reading. The purpose of this research is to explore the KWL (Know, Want, Learn) strategies for students' reading comprehension skills using the literature study method. The literature study is an activity relating to the method of collecting library data, reading materials, making some notes, and managing research materials. The data obtained was concluded and compared to find out research that is in accordance with the purpose of the research. The results of the assessment conducted show that the KWL (Know, Want, Learn) strategy provides a positive effect on reading comprehension. Students are more active in reading comprehension; students are easier to read and understand the contents of the text and students are easier to summarize the content of the texts. Kata kunci : KWL Strategy (Know, Want, Learn), Ability, Reading Comprehension